Analysis of anticaries potential of pit and fissures sealants containing amorphous calcium phosphate using synchrotron microtomography - Delben, A. C. B. [UNESP]; Cannon, M.; Vieira, A. E. M. [UNESP]; Basso, M. D. [UNESP]; Danelon, M. [UNESP]; Santo, M. R. E. [UNESP]; Stock, S. R.; Xiao, X.; De Carlo, F. (Operative Dentistry Inc, 2015)
The aim of this study was to analyze the anticaries potential of pit and fissure sealants containing amorphous calcium phosphate (ACP) by synchrotron microtomography. Bovine enamel blocks (4x4 mm; n=50) were selected through surface hardness (Knoop) analysis. Slabs were obtained through cross-sections taken 1 mm from the border of the enamel. Five indentations, spaced 100 mu m apart, were made 300 mu m from the border. Ten specimens were prepared for each tested material (Ultraseal XT plus TM, Aegis, Embrace, Vitremer and Experimental Sealant). The materials were randomly attached to the sectioned surfaces of the enamel blocks and fixed with sticky wax. The specimens were submitted to pH cycling. After that, the surface hardness (SH1) was determined, and the blocks were submitted to synchrotron microcomputed tomography analysis to calculate the mineral concentration (Delta g(HAp) cm(-3)) at different areas of the enamel. The comparison between the SH1 and DgHAp cm(-3) showed a correlation for all groups (r=0.840; p<0.001). The fluoride groups presented positive values of DgHAp cm(-3), indicating a mineral gain that was observed mainly in the outer part of the enamel. The ACP showed mineral loss in the outer enamel compared with fluoride groups, although it inhibited the demineralization in the deeper areas of enamel. The combination of two remineralizing agents (fluoride and ACP) was highly effective in preventing demineralization.